2005
DOI: 10.1002/bin.173
|View full text |Cite
|
Sign up to set email alerts
|

Impulsivity, self‐control, and delay discounting in persons with acquired brain injury

Abstract: The present paper describes two studies in which participants with and without acquired brain injuries were compared on a temporal discounting task involving various hypothetical amounts of money available at varying delay values. During Experiment 1, both groups of participants were presented with choices between amounts of money ranging from 1 to 1000 US dollars at delays from 1 week to 10 years. The results obtained from this procedure were consistent with previous models of temporal delay discounting for c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 21 publications
1
23
0
Order By: Relevance
“…Delay-discounting data for 11% of the sample (9 participants; 5 smokers) were not included in analyses for failure to meet data-validity criteria (see Dixon et al, 2003;2005). To be retained, a participant's discounting data were required to have indifference points that decreased in monetary value over at least two successive delays and to also not have indifference points that increased in monetary value more than once over successive delays.…”
Section: Resultsmentioning
confidence: 99%
“…Delay-discounting data for 11% of the sample (9 participants; 5 smokers) were not included in analyses for failure to meet data-validity criteria (see Dixon et al, 2003;2005). To be retained, a participant's discounting data were required to have indifference points that decreased in monetary value over at least two successive delays and to also not have indifference points that increased in monetary value more than once over successive delays.…”
Section: Resultsmentioning
confidence: 99%
“…The DD task is a behavioral analytic approach to understand how each individual makes a choice between a smaller reward given immediately and a larger reward given after a time delay, thus assessing the degree of cognitive impulsivity or self-control (Dixon et al, 2005). The task was composed of 120 trials; in each trial, the amounts of monetary reward for immediate and delay options are decided by the fixed k value and the delay time based on the hyperbolic function of delay discount, V ¼ A/(1 þ kD), where V is the value of the delayed outcome (ie, the indifference value), A is the delayed reward, D is the length of the delay, and k expresses the steepness of the discount function (Mitchell, 1999;Richards et al, 1999;de Wit et al, 2002).…”
Section: Dd Taskmentioning
confidence: 99%
“…The only explanation found for the lack of the magnitude effect in the clinical control group, is the possibility that the relatively small difference between discounted amounts could contribute to two things: a relatively small magnitude effect in groups, and a different trend in patients with frontal lobe damage. We used such amounts to make them as meaningful and easy to imagine to participants as possible, and based our approach on the study by Dixon et al (2005) that showed that when the reward is too large, patients with brain damage, may discount it in a more unsystematic way. Also, according to Sellitto et al, 2010 it is worthy to test delay discounting rate in patients with ventromedial orbitofrontal cortex (vmOFC) damage to obtain more insight to the neural mechanism of discounting.…”
Section: Discussionmentioning
confidence: 99%
“…This also applies to the processes of discounting, which can provide conceptual space for impulsive behavior (Dixon et al, 2005;McHugh & Wood, 2008;Sellitto, Ciaramelli & di Pellegrino, 2010;Peters & D'Esposito, 2016). The first empirical attempts to relate brain damage to impulsivity investigated the overall effect of the brain injury itself, regardless of specific localization.…”
Section: Introductionmentioning
confidence: 99%